1991
DOI: 10.1002/anie.199113451
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Interaction of Triplet 3‐Methylcyclohex‐2‐en‐1‐one with Maleo‐ and fumarodinitrile: Evidence for Direct Formation of Triplet 1,4‐Biradicals in [2 + 2] Photocyclo‐ additions without the Intermediacy of Exciplexes

Abstract: which has elsewhere['41 manifested a special coordination ability. Irradiation (d = 289 nm) of [Cr(C0),(q4-nbd)] and ECO in 2-methylpentane at -40°C affords mer-and juc-[Cr(C0),(q4-nbd) (q2-eco)], which are easily distinguished on the basis of their CO stretching bands (rner complex, f [cm-'] = 1997(m), 1925 (sst); fac complex < [cm-'] = 1968, 1904, 1876). The mer complex, which is more stable, is the only observed product at room temperature. In order to determine the quantum yield (@ = 0.18 at 300 nm, 0.1 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Evidence for triplet exciplexes in photocycloadditions has been indirect, and none has been observed directly in a cycloaddition system. Schuster has questioned the need for these intermediates in cyclohexenone photoannelation, and Peters , has interpreted the quenching of ketone triplets by electron rich alkenes as direct formation of a biradical. Biradical-trapping studies have led Weedon to conclude that exciplexes are not a requirement in explaining the regiochemical outcome of enone−alkene photoannelations.…”
mentioning
confidence: 99%
“…Evidence for triplet exciplexes in photocycloadditions has been indirect, and none has been observed directly in a cycloaddition system. Schuster has questioned the need for these intermediates in cyclohexenone photoannelation, and Peters , has interpreted the quenching of ketone triplets by electron rich alkenes as direct formation of a biradical. Biradical-trapping studies have led Weedon to conclude that exciplexes are not a requirement in explaining the regiochemical outcome of enone−alkene photoannelations.…”
mentioning
confidence: 99%
“…The extinction coefficient of the transient under investigation (ε T ) was determined using eqn. (3).…”
Section: Photophysical Measurementsmentioning
confidence: 99%
“…2 There is also interest in the mechanism of such reactions and there has been considerable discussion on the possible roles of exciplexes and biradical intermediates. 3,4 In this context 3-phenylcyclopent-2-enones are of interest as they undergo similar reactions and it has been shown that on excitation the parent compound 1 affords a triplet state which has an exceptionally long lifetime compared with those of other enones. 5 This may be caused by conjugation between the phenyl group and the enone which inhibits twisting in the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…10 for triplet energy transfer to acyclic 1,3-dienes in related systems are typically about lo8 M-' s-' (8). Rudolph and Weedon (1) also showed a plot of the inverse quantum yield for deconjugation of l a in benzene vs. the inverse concentration of acetic acid.…”
Section: A Continuous Irradiationsmentioning
confidence: 99%